Numerical Study of Soil Bearing Capacity for Conical Shell Foundation on Sandy Soil - غبشة, ديانا; رامي العبده, (Latakia University Journal -Engineering Sciences Series, 2025)
Previous theoretical studies have shown the importance of conical shell foundations as an economical and effective alternative to traditional foundations especially in areas suffering from high construction material costs or weak soil conditions. Conical shell foundations are widely used in countries like India and Siberia due to their superiority in load transfer on weak soil. In contrast, it is used very limitedly in many countries due to the difficulty and precision required for its implementation on one hand, and the lack of a precise understanding of its behavior and how to determine the soil bearing capacity beneath it on the other hand. Therefore, in this research, we conducted a numerical study using the finite element method and the PLAXIS 2D program for a conical shell foundation resting on sandy soil, examining the impact of various soil and foundation parameters on soil bearing capacity. The study investigated the effects of soil properties in terms of relative density, the impact of interface roughness, foundation height, and the influence of protrusions and peak angle. The Indian code stipulates that the ratio of height to radius (f/b) should be between 0.5 and 1. According to the parametric study, it has been shown that the bearing capacity increases as the ratio increases from 0.5 to 0.75. Beyond this point, any further increase in the ratio has no significant effect on the bearing capacity of a conical shell foundation resting on sandy soil. The results were analyzed to determine the optimal conditions for designing conical shell foundations contributing to improved structural performance and reduced costs. This study represents an important step towards developing of foundation shapes and more efficient and suitable design methods in the field of civil engineering.